Stock returns and the extent of compliance with IFRS 101 Standard among Malaysian Ace Market companies - Lode, Nor Asma; Abdul Rahman, Azhar; Othman, Omar (Universiti Utara Malaysia, 2012)
Malaysian is on the track to achieve full convergence and adoption of the International Financial Reporting Standards (IFRSs) by 2012.This study seeks to find out the extent of compliance with IFRS 101 ‘Presentation of Financial Statements’ before the effective date.Using total disclosure index (TDI), the findings show that most of Malaysian Ace Market companies have been complied with IFRS 101.The present study also indicates that Cumulative Market Adjusted Return (CMAR) is positive and significant for both partial and full compliance of IFRS 101 among Malaysian Ace Market companies.Multivariate regression analysis further provides a lack of significant association between CMAR and announcement of earnings (i.e. EPS). Nevertheless, percentage of independent directors on the board (BDIND) is found to be positive and significant corporate governance variable that associates with CMAR.